Diagnosis and pictorial key for the species of the genus Anastrepha Schiner, 1868 (Dipteral: Tephritidae) of economic importance in Venezuela - Caraballo, Josefina (ENTOMOTROPICA, 2007)
A pictorial key, with its respective glossary of terms, for separating the major fruit pest species of the genus Anastrepha Schiner, 1868 in Venezuela is presented: A. striata Schiner, 1868 in guava; A fraterculus (Wiedemann, 1830) in peach, mango, mombin plum and other fruits; A. obliqua (Macquart, 1835) in mango and mombin plum, and A. serpentina (Wiedemann, 1830) in naseberry, star apple and other Sapotaceae. Species considered as potential pests are also included: A. pickeli Costa Lima, 1934 and A. manhioti, Costa Lima, 1934 in cassava; A. grandis (Macquart, 1846) in squash and A. limae Stone, 1942 in passion fruit. Diagnostic characters are described for each species and host plant information is reviewed.